AC losses and induced fields in HTS coil wound using two-ply coated conductors. (June 2020) - Yokoyama, H; Zhu, B; Kajikawa, K; Awaji, S; Badel, A; Takahashi, K; Okada, T
Abstract: AC losses and screening-current-induced fields (SCFs) in a high temperature superconducting (HTS) inserts for high field magnet are evaluated theoretically. The HTS inserts are composed of stacked pancake coils, which are wound using two-ply conductors, where the superconducting-layer sides of two rare-earth-based coated conductors are attached to each other without electrical insulation. The theoretical formulas of AC loss and SCF in the two-ply conductor are derived for the simultaneous applications of a transport current and an external magnetic field parallel to its broad face. By taking into account the magnetic-field profile in the HTS insert and the magnetic-field dependency of critical current density in the coated conductor, the AC losses and SCFs are estimated using the theoretical formulas for monotonical increase in a central field up to 25.5 T in 60 minutes in combination with low temperature superconducting outsert coils. It is guessed that the AC loss estimated for the HTS insert wound using the two-ply conductor could be cooled by using prepared cryocoolers. The magnitude of SCF in the HTS insert wound using the two-ply conductor becomes smaller than that for the single-tape conductor estimated previously.